Faktor yang mempengaruhi kinerja perusahaan manufaktur yang terdaftar di bei - Marissa Karen, Merry Susanti (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence about the effect of capital structure, firm size, board size, current ratio and total asset turnover on firm performance of the manufacture companies listed in Indonesia Stock Exchange in the period of 2015-2017. This research used 48 manufacture companies that were selected using purposive sampling method of total 144 data in three years. The data used in this research are secondary data in the form of financial statements. The results of this research showed that firm size (SIZE), current ratio (CR) and total asset turnover (TATO) have a positive effect on firm performance (ROE). In contrast, capital structure (DER) and board size do not have an effect on firm performance of manufacture companies.